Mixed lubrication of steel by C18 fatty acids revisited. Part II: Influence of some key parameters. (February 2016) - Loehlé, S.; Matta, C.; Minfray, C.; Le Mogne, T.; Iovine, R.; Obara, Y.; Miyamoto, A.; Martin, J.M.
Abstract: The lubrication mechanism of iron-based materials by C18 fatty acids was investigated using experimental studies and computer simulations. In part I of this work [S. Loehlé et al., Trib. Int. 82(2015)218–227], the adsorption of fatty acids on iron oxide and the conditions to generate a strongly bonded Self-Assembled Monolayer (SAM) were studied. In this second part, the influence of several parameters on this adsorption mechanism of C18 fatty acids on steel-based surfaces was investigated. Among them, the effect of the degree of unsaturation in the alkyl chain, as well as the impact of the density of molecules adsorbed on the surface and the influence of the substrate composition (type of iron oxide/hydroxide), were examined. Then, the tribological behavior of adsorbed SAM was studied. It was confirmed that unsaturation in the alkyl chain leads to steric effects that inhibit the formation of well-organized monolayers and increase friction. The importance of the substrate composition on the adsorption mechanism of fatty acids on steel-based surfaces was also highlighted. Simulation results provide new insight into the in situ behavior of the molecules inside the contact, adding to the understanding of their tribological behavior. Highlights: We simulate the generation of an adsorbed layer of C18 fatty acids on iron-based surfaces. In situ adsorption followed by XPS analysis is performed to validate the model. When the degree of oxidation or hydroxylation increases, the reactivity between C18 fatty acids and the surface decreases. Steric effects induced by unsaturation prevent the formation of a well-arranged monolayer. Tribotests and molecular dynamic simulation show that stearic acid has the best tribological behavior on iron oxide surface.